Pengaruh Tata Kelola Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Healthcare Yang Terdaftar Di Bursa Efek Indonesia Periode 2022-2024 - Rina Oktaviany; Imam Malik; Ella Rahmayanti (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
This study aims to analyze the influence of corporate governance on tax avoidance in healthcare companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research was conducted from January 2025 to August 2025. This study uses a quantitative approach with secondary data in the form of annual financial reports from 28 companies selected through purposive sampling. The analytical method employed is panel data regression using EViews 12 software. Based on the results, the audit committee does not have a partial effect on tax avoidance in healthcare companies. This is indicated by the t-statistic value of -2.18E-14 with a significance level of 1.0000 (> 0.05). The proportion of independent commissioners also does not have a partial effect on tax avoidance, as shown by a t-statistic value of -1.241364 with a significance level of 0.2181 (> 0.05). Furthermore, audit quality does not have a partial effect on tax avoidance either, indicated by a t-statistic value of -1.230384 with a significance level of 0.2222 (> 0.05). In addition, the audit committee, the proportion of independent commissioners, and audit quality do not have a simultaneous and significant effect on tax avoidance, as evidenced by an F-statistic value of 1.289113 and a Prob. (F-statistic) of 0.283868 (> 0.05). The correlation coefficient (R) and the Adjusted R-Squared value is 0.010, indicating a moderate relationship between the independent and dependent variables, where the independent variables (audit committee, proportion of independent commissioners, and audit quality) explain only 0.01% of the variance in the dependent variable (tax avoidance), while the remaining 99.99% is explained by other variables not examined in this study.